Analysing The Effect of Investor Sentiment on the Co-Volatility of BRICS and the US Stock Markets - Goolam, Ammaarah; Ferreira-Schenk, Sune; Fabian Moodley; Matlhaku, Kago (The Journal of Accounting and Management, 2025)
Investor sentiment has a significant impact on the volatility of stock markets, as sentiment-driven investors are seen as irrational traders. Irrational trading in stock markets leads to market mispricing, causing market volatility, as investors base their decisions on their own expectations. This study aims to analyse the effect of investor sentiment on the covolatility of the BRICS and US stock markets during the COVID-19 period. To examine the impact of investor sentiment on volatility in the stock markets, the generalized autoregressive conditional heteroscedasticity (GARCH) models were utilised, incorporate a global sentiment index using daily market returns. The results show that investor sentiment has a significant impact on the covolatility between the BRICS and US stock markets. As a result, behavioural finance can be used to explain volatility in the BRICS and US stock markets. Therefore, it is recommended that portfolio managers in the financial industry incorporate a sentiment factor into asset pricing models, as sentiment was found to have a significant influence on pricing.